The Effect of Teamwork on Employee Performance Among Small and Medium Enterprises in Kampala: A Case Study at Exquisite Solution Limited - Clara Splendor Kaganzi (Uganda Christian University, 2023)
This study focused on the effect of teamwork on employee performance among Small and Medium Enterprises in Kampala. A case study at Exquisite Solution Limited. The objectives of the study were; to establish if effective communication in teams has an impact on the employee performance at ESL, to identify the effect of leadership in teams on the employee performance at ESL and to analyze the role of reward management in teams on employee performance at ESL. The study employed a descriptive research design since the analysis unit was based on only one firm. A case study design was used to select a sample size of 50 respondents and Purposive and Simple random sampling procedures were used. Secondary data was collected and it’s what was used to explain the research phenomenon. The study concluded that the worker productivity increases when there is effective communication among the teams and within the organization. Besides many other things the communication within the organization helps the employees to perform their tasks well, to have information about the duties they have to perform, and about the goals of the organization. They argue that existence of communication within the organization lead to the effective decision making. The study concluded that the worker productivity increases when there is effective communication among the teams and within the organization. The study examined and evaluated the effect of teamwork on Employee Performance among Small and Medium Enterprises in Kampala, a case study of Exquisite Solution Limited. Based on the findings, there is a positive and significant relationship between effective communication and employee performance. Therefore, effective communication in the entertainment industry is an essential tactic that has been performed which can extract the ultimate of the employee to help the both organization and the employees to achieve their ultimate goal. Level of trust has a positive and significant relationship with employee performance as referring to the findings. Building trust is building the confidence in each other’s competencies and reliabilities, thus, the existence of trust among team members constructs synergy in the organization and a better performance of its employees as trust in based on the reliability and the competencies.
This is a dissertation